Температурная зависимость твердости интерметаллидов с участием Al и некоторых эвтектических сплавов на их основе - Мордовец, Н.М. (Видавничий дім "Академперіодика" НАН України, 2008)
Temperature dependences of the hardness of the intermetallics Ni3Al, TiAl, and Al63Ti26Cr11 (L12-type) and the eutectic alloys Al53Ti21Cr26 (L12 + β), (β - solid solution on the base of chromium) and AlxTiyCrz (V, Mn, Re) (L12 + β) have been obtained in a wide region of temperatures (from the liquid nitrogen temperature to the temperature of recrystallization). On the base of these dependences, the activation energy of dislocation motion U0, activation volume V , characteristic temperature of deformation T*, and other physical parameters of alloys have been calculated. The values of the activation energy of dislocation motion are near to values of U0 for transition metals with bcc lattices, and the values of activation volumes are near to b³ (b - Burgers vector), as for bcc-metals. This is the evidence of a big value of the covalent part of interatomic bonds for these alloys.